The Effect of Platelet-Rich Plasma Injection as Therapy for Stress Urinary Incontinence Cases - Lubis, Munawar Adhar; Sumarlin, Sofi; Fakhrizal, Edy (Jurnal Ilmu Kedokteran, 2025)
Women frequently have stress urinary incontinence (SUI), which has a major negative influence on their quality of life. A non-surgical method of enhancing SUI that shows potential is platelet-rich plasma (PRP) therapy, by improving urethral tissue strength and enhancing the urethral closure mechanism. The usefulness of PRP in increasing urethral resistance and lowering SUI symptoms has been examined in recent literature studies conducted between 2019 and 2023. Although the first results are encouraging, more investigation is required to validate long-term advantages and clinical efficacy in broader groups, as well as to comprehend possible adverse effects and related difficulties. For SUI patients looking for non-surgical options, PRP offers an alluring treatment option with the potential to lessen the need for invasive surgical procedures. However, further development and broader clinical studies are necessary to strengthen these findings and support the clinical use of PRP in the management of SUI to improve quality of life.